(3CSQGQ GdYQHjIs - (3YHO GdQMef Hf eMeO Hf YHjO Gddg GdCfUGQj , GHf GdCfHGQj, ceGd GdOjf CHh GdHQcGJ,J (B577 (3g` s ((3eMeO Hf eMehO Hf eMeO GdeOYh HJGL GdcQejfi s)
(3ChdgG (B:s
(3HHGH EYQGH GdCaYGd Ef bGd bGFd de cGfJ GdCbhGd KdGKI eGVmi hMGVQ heSJbHd dEf GdCRefI deG cGfJ KdGKI hLH Cf jchf GdCbhGd KdGKI eGVi hMGVQ heSJbHd s
(3BNQgG (B:s
(3jQjOhf Ydi GdeGA hgPG djS HeWQO ai GdbjGS hEfeG OYGge Edi Pdc cKQI GdESJYeGd hgh ef GdTGP GdPi dG jbGS Ydjg aGYQag Je cJGH CSQGQ GdYQHjI HMeO Gddg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdfMhs